2009
DOI: 10.1080/09637480802516191
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic index of some commercially available rice and rice products in Great Britain

Abstract: The glycaemic response to nine types of rice (white basmati, brown basmati, white and brown basmati, easy-cook basmati, basmati and wild rice, long-grain rice, easy-cook long-grain rice, Thai red rice, Thai glutinous rice) and two types of rice vermicelli (Guilin rice vermicelli, Jiangxi rice vermicelli) commercially available in the United Kingdom were compared against a glucose standard in a non-blind, randomized, repeated-measure, crossover design trial. Fourteen healthy subjects (six males, eight females),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 35 publications
7
45
0
1
Order By: Relevance
“…Longer cooking times may result in a greater gelatinisation of the starch and help increase the glycaemic response. Indeed, this effect of increased cooking time on GI elevation has been put forward by Ranawana et al (2009) and can be supported by data from Panlasigui et al (1991). It is well known that amylose and amylopectin content can also affect the GI.…”
Section: Discussionsupporting
confidence: 57%
“…Longer cooking times may result in a greater gelatinisation of the starch and help increase the glycaemic response. Indeed, this effect of increased cooking time on GI elevation has been put forward by Ranawana et al (2009) and can be supported by data from Panlasigui et al (1991). It is well known that amylose and amylopectin content can also affect the GI.…”
Section: Discussionsupporting
confidence: 57%
“…The differences were not due to unabsorbed carbohydrate but were related to their physicochemical properties, such as gelatinization temperature, minimum cooking time, amylograph consistency, and volume expansion upon cooking. 16,54,63 They concluded that amylose content alone was not a good predictor of the starch digestion rate or glycemic response. Rice varieties with similar high amylose contents can differ in physicochemical (gelatinization) properties, and these in turn can influence starch digestibility and the blood glucose response.…”
Section: Gi and The Cooking Of Rice: Gelatinizationmentioning
confidence: 97%
“…57 Numerous processing conditions and storage in a cool environment may result in up to 30% starch retrogradation -that is, crystallization of the amorphous system created by gelatinization. 59 Ranawana et al 16 suggested that the gelatinized starch has not undergone sufficient retrogradation, resulting in a higher availability of digestible starch for gastrointestinal enzymes.…”
Section: Gi and The Cooking Of Rice: Gelatinizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice noodles in a broad sense have been identifi ed as intermediate to low glycemic index foods, with glycemic index values ranging from 37 (Ranawana et al , 2009) to 83 (Juliano, 2005). This occurs even without specifi c interventions to decrease starch digestibility.…”
Section: Rice Noodles and Resistant Starchmentioning
confidence: 99%